(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Epidemiology, as a foundational discipline within public health, holds paramount importance in understanding the distribution, determinants, and outcomes of health-related events in populations. This comprehensive overview elucidates the multifaceted role of epidemiology in safeguarding public health through its application in surveillance, outbreak investigation, risk factor identification, and health disparities research. Key topics include the evolution of epidemiology, study designs, surveillance systems, outbreak investigations, risk factor identification, and addressing health disparities. Furthermore, this overview discusses emerging challenges such as antimicrobial resistance and climate change, and proposes future directions for advancing the field.